2019
DOI: 10.7554/elife.46767
|View full text |Cite
|
Sign up to set email alerts
|

KHNYN is essential for the zinc finger antiviral protein (ZAP) to restrict HIV-1 containing clustered CpG dinucleotides

Abstract: CpG dinucleotides are suppressed in most vertebrate RNA viruses, including HIV-1, and introducing CpGs into RNA virus genomes inhibits their replication. The zinc finger antiviral protein (ZAP) binds regions of viral RNA containing CpGs and targets them for degradation. ZAP does not have enzymatic activity and recruits other cellular proteins to inhibit viral replication. We found that KHNYN, a protein with no previously known function, interacts with ZAP. KHNYN overexpression selectively inhibits HIV-1 contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
187
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 114 publications
(198 citation statements)
references
References 71 publications
(126 reference statements)
3
187
0
Order By: Relevance
“…For wild-type HIV-1, the magnitudes of inhibition were similar in the control and ZAP knockout cells ( Fig. 6A), which is consistent with the observation that endogenous ZAP does not target wild-type HIV-1 (16,31). The magnitude of IFN-I inhibition of HIV-1 env86 -561 CpG was reduced when ZAP was depleted, indicating that ZAP contributes to the antiviral effect of IFN-I on the virus.…”
supporting
confidence: 85%
See 4 more Smart Citations
“…For wild-type HIV-1, the magnitudes of inhibition were similar in the control and ZAP knockout cells ( Fig. 6A), which is consistent with the observation that endogenous ZAP does not target wild-type HIV-1 (16,31). The magnitude of IFN-I inhibition of HIV-1 env86 -561 CpG was reduced when ZAP was depleted, indicating that ZAP contributes to the antiviral effect of IFN-I on the virus.…”
supporting
confidence: 85%
“…It has previously been shown that introducing 36 CpGs into env nucleotides (nt) 86 to 561 (HIV-1 env86 -561 CpG) inhibits HIV-1 genomic-RNA abundance, Gag expression, Env expression, and infectious-virus production ( Fig. 3A, C, and E and Table 1) (16,31). Importantly, this restriction is eliminated in ZAP knockout cells ( Fig.…”
mentioning
confidence: 85%
See 3 more Smart Citations